A conceptual model of frugal innovation: is environmental munificence a missing link?. Issue 4 (4th December 2017) - Farooq, Rayees
Abstract : Purpose: The purpose of the study is to propose a conceptual model of frugal innovation and examine how it is linked to value creation. Design/methodology/approach: This study is exploratory in nature, whereby previous studies were explored to identify the dimensions of frugal innovation. The previous studies were explored from selected databases including Google Scholar and ProQuest using the key word search, "frugal innovation", "Jugaad innovation", "value creation" and "environmental munificence". The review process included the studies from 1991 to 2017. Findings: This study suggests that frugal innovation is a multidimensional construct with affordability, simplicity, quality, sustainability, resilience, management support and defeaturing as its dimensions. The study found that frugal innovation is an important predictor of value creation. The study also proposes the moderating effect of environmental munificence on the relationship between frugal innovation and value creation. Practical implications: This study invokes entrepreneurs, academicians and managers to be more inclined toward the bottom of the pyramid by using fewer resources. The study contributes to the strategic entrepreneurship literature by developing a conceptual framework of frugal innovation and linking it to the value creation. Originality/value: The conceptual framework proposed is based on selected dimensions which seem to be lacking owing to various conceptualizations and meanings in the literature. The study is the first of its kind which has proposed the dimensions of frugal innovation.